376. THE IMPACT OF OVERALL SURVIVAL ON TWO-FIELD OR THREE-FIELD LYMPHADENECTOMY IN MIDDLE AND LOWER THORACIC ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Li, Kexun; Leng, Xuefeng; Li, Changding; Liu, Kun; He, Wenwu; Luo, Xi; Wang, Chenghao; Wang, Qifeng; Wang, Kangning; Liu, Guangyuan; Zhou, Qiang; Jiang, Longlin; et al.
Abstract: More than 50% of esophageal cancer cases worldwide occur in China. Squamous cell carcinoma is the main subtype of esophageal cancer in East Asian. The manner of lymphadenectomy during surgery is related to the OS, but the effect of removed lymph node count for middle and lower thoracic esophageal squamous cell carcinoma (ESCC) in China is still controversial. Data were obtained from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database (SCH-ECCM Database) from Jan. 2010 to Dec. 2017. Patients were divided into two groups: For patients without suspicious tumor-positive cervical lymph nodes, 2-field systematic lymphadenectomy was performed and were belonged 2F group, while patients with suspicious tumor-positive cervical lymph nodes, 3-field systematic lymphadenectomy was performed and were put into 3F group. According to the quartile number of resected lymph nodes during operation. Four subgroups were designed for analysis in 2F group and 3F group, depending on the intensity of the lymphadenectomy. After 60.0 months (95% CI 56.5–63.4) of median follow-up time. The median OS of 2F group patients was 46.9 months (95% CI 39.3–54.5), 3F group was 34.0 months (95% CI 26.1–42.0). The OS at 1, 3, and 5 years were 87%, 57%, and 46% in the 2F group. In the 3F group, the OS rates at 1, 3, and 5 years were 82%, 49%, and 41% (P = 0.029). According to the quartile number of RLNs, there were different survival outcomes in 3F sub-groups, while in the 2F groups, the OS between A/B/C/D group was not significantly different (Fig A & B). ESCC patients with suspicious tumor-positive cervical lymph nodes have significantly worse OS than patients who without tumor-positive cervical lymph nodes. Different lymph nodes number removed in 3F patients could lead the entirely different survival outcomes. However, this still needs further large scale study to verify in China.